Neighborhood Quality and Attachment: Validation of the Revised Residential Environment Assessment Tool. (April 2017) - Poortinga, Wouter; Calve, Tatiana; Jones, Nikki; Lannon, Simon; Rees, Tabitha; Rodgers, Sarah E.; Lyons, Ronan A.; Johnson, Rhodri
Various studies have shown that neighborhood quality is linked to neighborhood attachment and satisfaction. However, most have relied upon residents' own perceptions rather than independent observations of the neighborhood environment. This study examines the reliability and validity of the revised Residential Environment Assessment Tool (REAT 2.0), an audit instrument covering both public and private spaces of the neighborhood environment. The research shows that REAT 2.0 is a reliable, easy-to-use instrument and that most underlying constructs can be validated against residents' own neighborhood perceptions. The convergent validity of the instrument, which was tested against digital map data, can be improved for a number of miscellaneous urban form items. The research further found that neighborhood attachment was significantly associated with the overall REAT 2.0 score. This association can mainly be attributed to the property-level neighborhood quality and natural elements components. The research demonstrates the importance of private spaces in the outlook of the neighborhood environment.